2019
DOI: 10.1007/s00417-019-04299-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spectralis and Cirrus spectral domain optical coherence tomography for the objective morphometric assessment of the neuroretinal rim width

Abstract: Purpose The assessment of cup-disc ratio as a surrogate parameter for the neuroretinal rim width (NRW) of the optic nerve is well established, but prone to human error and imprecision. Objective assessment of the NRW is provided by spectral domain optical coherence tomography (SD-OCT). This study is the first to systematically compare NRW measurements acquired with the Carl Zeiss Meditech Cirrus HD-OCT 5000 and the Heidelberg Engineering Spectralis SD-OCT. Methods In this cross-sectional study, 20 eyes of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Traditionally, glaucoma has been considered as a disease specifically of RGCs, 24 27 although a growing number of studies support the notion that other retinal cell types may be affected in glaucoma pathology. 22 , 28 , 29 In this context, anomalies in electroretinography responses, including alterations in the a- and b-waves, scotopic threshold responses, and oscillatory potentials, have been described in both human disease and in experimental CG models, 12 , 22 , 30 – 35 suggesting dysfunction in different retinal cell types.…”
mentioning
confidence: 99%
“…Traditionally, glaucoma has been considered as a disease specifically of RGCs, 24 27 although a growing number of studies support the notion that other retinal cell types may be affected in glaucoma pathology. 22 , 28 , 29 In this context, anomalies in electroretinography responses, including alterations in the a- and b-waves, scotopic threshold responses, and oscillatory potentials, have been described in both human disease and in experimental CG models, 12 , 22 , 30 – 35 suggesting dysfunction in different retinal cell types.…”
mentioning
confidence: 99%
“…The GCL/IPL thickness ranges of the current study are in line with the previous glaucoma literature from both Cirrus 22,23 and Spectralis 24 studies. Furthermore, a trend of thicker Cirrus measurements compared with Spectralis has been shown in a neuroretinal rim‐width study of glaucoma patients and healthy controls 25 …”
Section: Discussionmentioning
confidence: 81%
“…13,15,18 Quantitative measurements of neuroretinal rim width or peripapillary retinal nerve fiber layer thicknesses have also demonstrated significantly different values between devices. 19,20 It has been suggested that the differences in resolution between devices can impact the performance of segmentation algorithms, thereby resulting in different layer thickness values.…”
Section: Discussionmentioning
confidence: 99%